The difference of free light chains as a predictor of kidney damage in patients with Multiple Myeloma - Salvatrice Mancuso; Melania Carlisi; Nicola Serra; Mariano Sardo; Giuseppe Bertuglia; Emanuela Pappalardo; Sergio Siragusa (Epidemiology, Biostatistics and Public Health)
Background: Multiple myeloma (MM) is a malignant neoplasm characterized by the clonal expansion of plasma cells that can release monoclonal immunoglobulins (monoclonal component) or part of theme. Since 2001, the k and λ serum free light chains (sFLC) evaluation and their ratio (rFLC) have made up the laboratory analysis more sensitive and precise in MM patients. The role of rFLC has been widely studied and discussed and now it is validated in the literature. Instead, the value of free light chains difference (dFLC), especially in MM is less known yet. The aim of this study is to evaluate the relationship between the dFLC and the kidney damage parameters in patients with MM, in comparison with the rFLC value.